(untitled) (European Journal of Pure and Applied Mathematics, 2024)
Our main purpose is to introduce the concepts of upper and lower weakly (τ_1,τ_2)-continuous multifunctions. Moreover, some characterizations of upper and lower weakly (τ_1,τ_2)-continuous multifunctions are investigated.